Intellectual Property Challenges for AI-Driven Creativity: A Focus on Copyright and Patents in Emerging Economies - Lu Sudirman; Hari Sutra Disemadi; Henry Soelistyo Budi; Jihyun Park; Ninne Zahara Silviani (Lex Scientia Law Review, 2025)
The integration of Artificial Intelligence (AI) into scientific advancements has become a crucial part of daily life for many people. In the creative industry, AI has the potential to not only enhance the level of creativity, but also productivity. The legal implications of this development must be carefully analyzed for the development of the creative industry, to establish a legal position on where AI stands in the increasingly competitive market, especially when Intellectual Property Right (IPR) as a key factor is taken into account. This research examines the need for a legal framework for AI. It was conducted through the lens of intellectual property law, to determine its place within existing IPR regimes using the comparative legal method. The results conceptually justify the urgency to regulate AI, and highlights the taxonomy dilemma of AI-generated works within the current dynamics of the creative industry, indicating a taxonomy dilemma. Further analysis also indicates that while there’s a decent urgency to address all of the normative issues that exist within Indonesia’s IPR legal framework, it’s imperative that Indonesia prioritizes the development of the copyright and patent regimes, which are closely related to the nature of AI-generated works.